Sidescan sonar survey (300 kHz) during R/V Heincke cruise HE505 in the German Bight with link to raw data files - Svenja Papenmeier; H Christian Hass (PANGAEA, 2019)
Sidescan sonar data were collected during R/V Heincke cruise HE505 with a towed multi pulse Edgetech 4200-MP. Data recording was executed along 79 parallel profiles in North Sea within German EEZ. The survey speed was ~5 knots and the swath set to 140 to 300 m depending on the study site to obtain a resolution of up to 25 cm along track. In total 96 km^2 were area-wide mapped.